Editorial (Thematic Issue: Recent Updates on Biologically Active Heterocycles - Part 2) - Shah, Anamik (Current Organic Chemistry, 2014)
In continuation with the earlier “Thematic Series - Bioactive Heterocycles, Part 1', this is the second Thematic Series on this vibrant area of bioactive heterocyclic entities. Diversity-oriented synthesis (DOS) is a thriving field involving the preparation of chemical libraries of versatile small molecules for biological screening. The last decade has witnessed tremendous progress in the field, with continued emphasis on structural and functional diversity for DOS library construction. A number of recent reviews have updated the synthetic organic chemists on this topic, including recent successes of biologically active molecules obtained from DOS compound collections. The role of multifaceted coumarin synthesized by DOS, the bioisostere of naturally occurring Calanolide A and B, as a privileged class of compounds was proven to be significant for dormant tuberculosis. The therapeutic significance of guanidines synthesized by DOS as antiprotozoal and antiparasitic is well-established while its significant role in neglected tropical diseases (NTDs), such as human african trypanosomiasis, chagas disease, leishmaniasis, buruli ulcer,echinococcosis, taeniasis/cysticercosis, lymphatic filariasis and onchocerciasis has been summarized extensively. The importance of 1-aryl propargylic alcohols as a key building block in the constructions of bioactive five- and six-membered heterocycles has been scrutinized. In the area of peptidomimetics, a new class of amphiphilic peptides, both in linear and rigid form and its nanoparticles was synthesized for biomaterial sciences and biomedicines study. Nano-composites have exceptionally high surface to volume ratio. The role of nanocomposites in the synthesis of bioactive precursors via green technology assisted by ultrasound methodology might prove worthy for its application in drug discovery. The contribution of various authors across the globe is quite noteworthy to make this issue very rich for all who are working at the interface of chemistry and biology. Taken collectively, Bioactive Heterocycles embodies a broad, vibrant and continual growing scientific area with this Thematic Issue is highlighting recent advances in the field. As a Guest Editor of this Thematic Issue (Part 1 & 2), I would like to thank authors for their excellent scientific contributions and make this issue successful. I am also indebted for secretarial assistance from Dr. Atul Manvar and other research scholars of my research group at the National Facility for Drug Discovery Centre, Saurashtra University, Rajkot. Lastly, I thank Bentham Science Publishers for their excellent professional support.